Review Meeting with States/UTs on Integrated Rural Energy Programme Background Note, 4th December 1992 - Planning Commission (Planning Commission, 1992)
The Integrated Rural Energy Programme (IREP) in India aims to enhance rural energy access by combining conventional and renewable energy sources, focusing on domestic needs and productive activities. Key features include geographical expansion, technical and financial support, community engagement, and environmental considerations. Robust training frameworks have been established at national, regional, and local levels to strengthen planning and implementation capabilities. Financial allocations include Rs. 250 crores for institutional development and Rs. 500 crores for the Minimum Needs Programme targeting below-poverty-line families. Installations under the State Sector encompass a wide array of renewable energy devices such as domestic improved chulahs, portable wood stoves, biogas plants, solar water heaters, and solar street lights across multiple states, improving domestic energy security and reducing reliance on traditional fuels. The programme emphasizes monitoring, stakeholder engagement, and integration with broader rural development initiatives to ensure long-term sustainability and enhanced quality of life in rural India.
Planning Commission Rural Energy Division New Delhi
Planning Commission Rural Energy Division New Delhi
Keywords: Integrated Rural Energy Programme; Rural Energy Access; Renewable Energy Technologies; Domestic Improved Chulahs; Biogas Plants; Solar Water Heaters; Community Participation; Training Framework; Environmental Sustainability; State Sector Installations